Citizen’s Income (“Bürgergeld”) or Social Welfare (“Hartz IV”)? - Holger Schäfer (Wirtschaftsdienst)
Abstract Germany’s new government attempts once again to get rid of the infamous “Hartz IV” name for the country’s basic income support. The new “Bürgergeld” not only sports a new name, it also formulates new rules for sanctions and for considering income and property.